Design and Analysis of Ultrasonic Composite Transducer with a Quarter-wave Taper Transition Horn - CHEN, Tao; LI, Hongbo; WANG, Qihan; YE, Junpeng (Archives of Acoustics, 2020)
Based on the electromechanical equivalent circuit theory, equations related to the resonance frequency and the magnifying coefficient of a quarter-wave vibrator and a quarter-wave taper transition horn were deduced, respectively. A series of 3D models of ultrasonic composite transducers with various conical section length was also established. To reveal the influences of the conical section length and the prestressed bolt on the dynamic characteristics (resonance frequency, amplitude, displacement node, and the maximum equivalent stress) of the models and the design accuracy, finite element (FE) analyses were carried out. The results show that the addition of prestressed bolt increases the resonance frequency and causes the displacement node on the center axis to move towards the small cylindrical section. As the conical section length rises, the increment of resonance frequency reduces and tends to a stable value of 360 Hz while the displacement of the node on the center axis becomes lager and gradually approaches 1.5 mm. Furthermore, the amplitude of the output terminal is stable at 16.18 μm under 220 V peak-topeak (77.8 VRMS) sinusoidal potential excitation. After that, a prototype was fabricated and validated experiments were conducted. The experimental results are consistent with that of theory and simulations. It provides theoretical basis for the design and optimization of small-size, large-amplitude, and high-power composite transducers.